The Influence of Servant Leadership and Organizational Culture on Employee Performance at ODSK Regional General Hospital in North Sulawesi - Saharui, Fanny Maria Louise; Bogar, Wilson; Mokat, Jetty E. H. (Technium Social Sciences Journal, 2024)
This study aims to determine (1) The influence of servant leadership on the performance of employees of the ODSK Regional General Hospital, North Sulawesi Province. (2) To determine the influence of organizational culture on the performance employees of the ODSK Regional General Hospital, North Sulawesi Province. (3) To determine the influence of servant leadership and organizational culture together on the performance of employees of the ODSK Regional General Hospital, North Sulawesi Province. The research method employed is a survey method using questionnaires designed in a Likert scale format. The respondents of the study consisted of 137 employees selected through proportional random sampling. The analysis used to test the research hypotheses includes simple and multiple regression and correlation techniques. The conclusions of this study indicate that (1) Servant Leadership has a positive and significant effect on employee performance. (2) Organizational Culture has a positive and significant effect on employee performance. (3) To determine the joint influence of servant leadership and organizational culture on the performance of employees at ODSK Provincial General Hospital in North Sulawesi. Recommendations: (1) Foster mutually supportive relationships between leaders and employees, as well as among employees, through harmonious interactions. (2) Build an organizational culture that encourages employees to stay and work effectively. (3) Enhance employee performance through servant leadership and organizational culture initiatives implemented simultaneously.